2005
DOI: 10.1208/pt060239
|View full text |Cite
|
Sign up to set email alerts
|

Process analytical technology case study, part III: Calibration monitoring and transfer

Abstract: This is the third of a series of articles detailing the development of near-infrared spectroscopy methods for solid dosage form analysis. Experiments were conducted at the Duquesne University Center for Pharmaceutical Technology to develop a system for continuous calibration monitoring and formulate an appropriate strategy for calibration transfer. Indicators of high-flux noise (noise factor level) and wavelength uncertainty were developed. These measurements, in combination with Hotelling's T(2) and Q residua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…Moreover, potential differences in the spectral process signatures [10] for production-and laboratory-scale samples introduce an additional opportunity for prediction error, especially as the laboratory-scale samples will account for the greatest portion of leverage in the calibration dataset. Furthermore, even a well-designed calibration, having controlled variation in many critical factors, can be expected to require periodic maintenance [8,11,12]. While it is straightforward to design a set of tablets covering all degrees of freedom in the space of composition variation, it can be more difficult to anticipate or control the myriad other factors that may impact tablet NIR spectra.…”
Section: Rationale For Finished Product Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, potential differences in the spectral process signatures [10] for production-and laboratory-scale samples introduce an additional opportunity for prediction error, especially as the laboratory-scale samples will account for the greatest portion of leverage in the calibration dataset. Furthermore, even a well-designed calibration, having controlled variation in many critical factors, can be expected to require periodic maintenance [8,11,12]. While it is straightforward to design a set of tablets covering all degrees of freedom in the space of composition variation, it can be more difficult to anticipate or control the myriad other factors that may impact tablet NIR spectra.…”
Section: Rationale For Finished Product Testingmentioning
confidence: 99%
“…2). Hence, there is always the possibility that a NIR calibration model may exhibit drift (slope or bias error), thereby, requiring correction or update [12] as process and measurement equipment age, environmental conditions change, or as new batches of raw materials are consumed. Fig.…”
Section: Rationale For Finished Product Testingmentioning
confidence: 99%
“…Numerous studies have been carried out to explore the use of NIRS for powder blending control. The fact that NIRS has great potential in this application has been shown by Wargo and Drennen [139][140][141][142]. Cho and co-workers dealt with the effective mass that is sampled by NIR fibre-optic reflectance probes in blending processes and demonstrated that the sampled mass met FDA requirements [143].…”
Section: Powder Blendingmentioning
confidence: 99%
“…However, it can also be used in a calibration transfer context, where directions in the data that correspond to instrumental differences are down -weighted. The use of GLS weighting for calibration transfer is discussed in reference [116] .…”
Section: Generalized L East S Quares ( Gls ) W Eightingmentioning
confidence: 99%